Coherent emission from fully Er 3+ doped monolithic 1-D dielectric microcavity fabricated by rf-sputtering - Stefano Taccheo (Optical Materials, 2018)
All Er3+ doped dielectric 1-D microcavity was fabricated by rf sputtering technique. The microcavity was constituted by half wave Er3+ doped SiO2 active layer inserted between two Bragg reflectors consists of ten pairs of SiO2/TiO2 layers also doped with Er3+ ions. The scanning electron microscopy was used to check the morphology of the structure. Transmission measurements confirm the third and first order cavity resonance at 530 nm and 1560 nm, respectively. The photoluminescence measurements were obtained by optically exciting at the third order cavity resonance using 514.5 nm Ar+ laser with an excitation angle of 30°. The Full Width at Half Maximum of the emission peak at 1560 nm decrease with the pump power until the spectral resolution of the detection system of ∼1.0 nm. Moreover, the emission intensity presents a non-linear behavior with the pump power and a threshold at about 24 mW was observed with saturation of the signal at above 185 mW of pump power.